A Multi-Method Approach for Quantification of In- and Exfiltration Rates from the Subterranean Estuary of a High Energy Beach - Grünenbaum, Nele; Ahrens, Janis; Beck, Melanie; Gilfedder, Benjamin Silas; Greskowiak, Janek; Kossack, Michael; Massmann, Gudrun (Frontiers in Earth Science, 2020)
Accurate SGD (submarine groundwater discharge) mass export calculations require detailed knowledge of the spatial and temporal variability in SGD rates. In coastal aquifers, SGD includes a terrestrial freshwater component as well as a saline component originating from circulating seawater. Representative field measurements of SGD rates are difficult to conduct, because SGD is often patchy, diffuse, and temporally variable, especially under tidal influence and high wave activity. In this study, a combination of lysimeters, seepage meters, temperature sensors, pore water radon, and numerical modelling was used to estimate the volumes of infiltrating seawater and exfiltrating groundwater in the intertidal zone of a mesotidal, high energy beach on Spiekeroog Island, northern Germany. Additionally, a 3D- laser scanner was used over short (days) and medium time scales (months) to determine changes in beach topography. The results showed net water infiltration above mean sea level (MSL) and net exfiltration below MSL. Water exchange rates fluctuated between 0.001 and 0.6 m d-1, showing similar ranges within the multiple method approaches. The beach topography was subject to strong fluctuation caused by waves, currents, wind driven erosion and sedimentation, even over short time scales. A comparison of extrapolated in- and exfiltrating water volumes along a beach transect from the mean high water to mean low water line at different times highlights the variability of total in or outflow. The results show that exchange rates depend on beach topography, which in turn changes significantly over time.